Leptospirosis pada Kucing di Yogyakarta dan Sekitarnya (FELINE LEPTOSPIROSIS IN YOGYAKARTA AND ITS SURRONDING) - Mulyani, Guntari Titik; Raharjo, Slamet; Purnomo, Agung Budi; Santoso, Yuli; Kurnia, Kurnia; Wirapratiwi, Dyah Kunti (Jurnal Veteriner; Vol 19 No 4 (2018)DO - 10.19087/jveteriner.2018.19.4.446, 2019)
Leptospirosis is a zoonotic disease that infects almost of mammals. The infecting microorganism is the Leptospira interrogans, which have many serovars. Clinical leptospirosis is rare in cats, but cats may shed leptospire in the urine to other animals, humans or environment. The aims of this research is to study feline leptospirosis in Yogyakarta and its surrounding. A total of 27 cats consisting of 3 groups of cats: household cats, stray cats, and cats with leptospirosis symptom were used in this research. The blood from all cats were taken 3 ml from cephalica vein, the serum were separated for Microscopic Agglutination Test (MAT). The examination were   conducted in Bbalitvet Bogor for 14 Leptospira serovar: Ichterohaemorrhagiae, Javanica, Celledoni, Ballum, Pyogenes, Cynopeteri, Rachmati, Australis, Pomona, Canicola, Grippotyphosa, Bataviae, Hardjo, dan Tarrasovi. The results showed that 1 stray cat was positive for Tarrasovi serovar. From the results of this study can be concluded that there was subclinic feline leptospirosis in Yogyakarta that caused by Leptospira interrogans Tarrasovi serovar.